FE analysis of stress and displacements occurring in the bony chain of leg - Filardi, Vincenzo (J Orthop, 2014)
AIMS: The aim of this study was to assess how the stress shielding can influence the integrity and resistance of bones. METHODS: With this purpose a complete FE model of the human leg was realised. A load of 700 N has been applied at the top of pelvis and the feet, at the tip, was rigidly fixed. RESULTS: Obtained results reveal interesting consequences deriving by taking into account the complete bony chain. CONCLUSION: A comparison among the literature data and our models can furnish a complete vision of the global spreading of the forces along the various bony components.